Effects of bromadiolone poisoning on the central nervous system - Wang M (Dove Medical Press, 2017)
Meiling Wang,1 Yanfeng Yang,2 Yiwei Hou,1 Wenbin Ma,1 Rui Jia,1 Jinbo Chen1 1Neurology Department, Binzhou Medical University Hospital, Binzhou Medical University, 2Binzhou Blood Center, Binzhou, China Abstract: Cases of rodenticide poisoning (second-generation long-acting dicoumarin rodenticide, superwarfarin) have occasionally been reported. The main symptoms of bromadiolone poisoning are skin mucosa hemorrhage, digestive tract hemorrhage, and hematuresis. However, the symptoms of central nervous system toxicity have rarely been reported. Our case reports on a 41-year-old male who had no contact with bromadiolone. His main symptoms were dizziness, unsteady gait, and abnormal behavior. Laboratory test results revealed the presence of bromadiolone in his blood and urine, a longer prothrombin time, activated partial thromboplastin time, and a high international normalized ratio. Magnetic resonance imaging of the brain showed that the bilateral posterior limb of the internal capsule, splenium of corporis callosum, and bilateral centrum semiovale formed symmetrical patch distribution. The patient gradually recovered after treated with vitamin K1 and plasma transfusion. Our clinical study could pave the way to improve the detection of bromadiolone poisoning and avoid misdiagnosis. Keywords: bromadiolone, poisoning, central nervous system, superwarfarin